Evaluation of veterinary antibiotic residues in commercial and local farms in Al-Bayda city, Libya (2024-2025), with a molecular docking study to analyze their effect on target microbial proteins - Abdulsalam Saleh; Rihab Ramadhan Farhat; Zafir AM Zafir; Randa Mahmoud; Mohammd Abd Alati; Hajir Othman (African Journal of Advanced Pure and Applied Sciences, 2025)
This study detected veterinary antibiotic residues (neomycin, penicillin, enrofloxacin) in 400 Libyan samples (200 eggs, 200 milk) using microbial inhibition and chromatographic techniques. Results showed significantly higher residues (p≤0.05) in local vs. commercial farms, with minimal reduction after boiling. Penicillin showed highest residues (milk: 55.23μg/ml local, 8.86μg/ml commercial; eggs: 46.88μg/g local, 11.44μg/g commercial). Molecular docking confirmed penicillin's strong ubiquitin binding (-5.7 kcal/mol), correlating with experimental data and validating computational approaches for residue prediction. Findings emphasize the need for stricter veterinary oversight and withdrawal period compliance.